Panjang Jimat: Cultural Tourism at Cirebon Palace - Prawira Triutama, Oqke; Bastoni, Bastoni; Hamidah, Nurul; Khairune Nisa, An Nuur (Jurnal Toursci, 2024)
This paper discusses how Panjang Jimat comes from the words "Panjang" and "Jimat". The word Panjang means the lifetime of man, while Jimat or "ji" or siji means one, and "mat" or crushed means something to be remembered, guarded, and preserved. So, Panjang Jimat means something or one that a lifetime of man must remember, guard, and defend. This research uses a qualitative method approach to describe the natural condition of objects, where the researcher is the key instrument. The reason researchers choose descriptive research is to be able to describe systematically and accurately facts and characteristics about the population or a particular field. The researcher here intends to provide an overview of a particular social phenomenon that already exists. Panjang Jimat as a custom of the Cirebon palace began in the 15th century to commemorate the birthday of the Prophet Muhammad SAW especially. At this time, Panjang Jimat ceremony was organized by the existence of the Kasepuhan Palace Foundation as a formal legal entity organization, further strengthening the identity of the Kasepuhan Palace today. This phenomenon is seen in the holding of Panjang Jimat Ceremony.